AB0176 Increased Toll-Like Receptor 5 Signalling and IL-6 Production in Monocytes from Patients with Systemic Lupus Erythematosus. (9th June 2015) - Davies, K.A.; Thwaites, R.; Emery, P.; Ponchel, F.; Sacre, S.
Abstract : Background: The innate immune system contributes to the pathogenesis of SLE, in part through the activity of Toll-like receptors (TLRs), a family of pattern-recognition receptors. Nucleic acid containing immune-complexes, which are characteristic of SLE, activate the RNA and DNA sensing TLRs 7 and 9, resulting in interferon production [1]. Although a role for interferon is well established in SLE, other cytokines such as interleukin (IL)-6 have also been shown to correlate with disease activity, with an anti-IL-6 receptor antibody (Tocilizumab) demonstrating some early success in clinical trials [2][3]. Objectives: TLR-7 and 9 are primarily considered drivers of IFN production, but in this study, our aim was to explore the biology of other key TLR's (4, 5 and 8) in SLE in vitro, specifically the role of these TLR's in the induction of interleukin-6 production by monocytes. Methods: Freshly-obtained peripheral blood monocytes from patients with known SLE (satisfying standard diagnostic and seroplogical criteria) were studied, contemporaneously with cells from healthy volunteers. TLR expression was evaluated by flow cytometry. Monocyte IL-6 production was measured by ELISA, and evaluation of mRNA levels, before and after in vitro stimulation with flagellin. Results: An increase in TLR5 expression (p<0.001; 30 patients and controls) and TLR5-induced IL-6 production was observed in SLE monocytes: (HC mean 0.311ng/ml; SLE mean 2.26ng/ml), p=0.0447; 31 patients, 19 controls). Additionally, downstream regulators of TLR5 signalling were also found to be dysregulated at the mRNA level in the patient samples, showing a direct correlation with TLR5 induced IL-6 production (p=0.0005, r 2 =0.515). Conclusions: These data suggest that there is altered expression and function of TLR5 in SLE patient monocytes. Our results indicate that this may be a factor contributing to incresaed IL-6 levels in the paient group, with potential pathogenic implications. With further charactertisation this pathway may be amenable to therapeutic modification in the future. References: Celhar, T. and A.M. Fairhurst, Toll-like receptors in systemic lupus erythematosus: potential for personalized treatment. Frontiers in pharmacology, 2014. 5: p. 265. Illei, G.G., et al., Tocilizumab in systemic lupus erythematosus: data on safety, preliminary efficacy, and impact on circulating plasma cells from an open-label phase I dosage-escalation study. Arthritis and rheumatism, 2010. 62(2): p. 542-52. Chun, H.Y., et al., Cytokine IL-6 and IL-10 as biomarkers in systemic lupus erythematosus. Journal of clinical immunology, 2007. 27(5): p. 461-6. Acknowledgements: Preliminary work was supported through the FP7 MASTERSWITCH programme. RT is funded by a BSMS studentship. We are grateful to the staff of the RSCH Clinical Investigation and Research Unit for their assistance. Disclosure of Interest: None declared